Pengaruh Alokasi Dana Desa terhadap Pertumbuhan Ekonomi Masyarakat Desa Lewolaga Kecamatan Tite Hena - Dionisius Duli Riang Petung; Andreas Rengga; Konstantinus Pati Sanga (Universitas Katolik Widya Karya Malang, 2023)
This research aims to test and analyze the influence between Village Fund Allocation and Economic Growth in Lewolaga village, Tite Hena District. This type of research is quantitative research with an associative approach, through statistical analysis by collecting secondary data regarding village fund allocation and economic growth data from Lewolaga village during the 2015 – 2022 period. The results of statistical analysis show that Village Fund Allocation has a significant influence on Economic Growth in Lewolaga village. Sig value. of the Village Fund Allocation Variable is 0.005 smaller than the significance level α=0.05, so the null hypothesis is rejected and the alternative hypothesis is accepted. The t value is 4,361, while the t table value (df 7; 0.05) is 1.89458, indicating that t count > t table, which confirms the existence of a significant difference between the two variables. This research provides important implications that Village Fund Allocations can be an effective instrument in encouraging economic growth in rural areas such as Lewolaga. The government and stakeholders are expected to optimize the use of village funds by prioritizing programs that contribute to local economic development. In the context of agency theory, community participation in decision making and active involvement of local economic actors are also key in increasing the effectiveness of village fund allocation to achieve better results in supporting economic growth at the Lewolaga village level.